Two new species of Diamesinae (Diptera: Chironomidae) from the Central Iranian Range and Elburz Mountains (Iran), with new faunistic records for the subfamily - Ghaderi, Edris; Namayandeh, Armin; Ibrahimi, Halil; Mohammadi, Habibollah; Karimian, Erfan; Mansouri, Arman; Molodi, Farshad (Zootaxa, 2024)
As part of our continuous investigation into the biodiversity of Chironomidae of Iran, we expanded our collection area to the Elburz Mountains and the Central Iranian Range in East Azerbaijan and Kurdistan Provinces. As a result of this, we discovered and described Diamesa sahandensis sp. nov. and Sympotthastia golalae sp. nov., two new Diamesinae, adding to the diversity of these genera in Iran and the Palaearctic region. We also provide new Iranian faunistic records, Diamesa kasymovi Kownacka et Kownacki, 1973, describe its female for the first time, and provide an updated key to the adult males of Sympotthastia Pagast, 1947. Based on the molecular analysis of cytochrome oxidase (COI) genes and methods for delimiting species, the average interspecific distance between S. golalae sp. nov. and other species of Sympotthastia was high enough (13.9%) to maintain a species level.